(E)‐4‐Bromo‐2‐[(phenylimino)methyl]phenol: a new polymorph and thermochromism. Issue 11 (8th October 2020) - Mason, Helen E.; Howard, Judith A. K.; Sparkes, Hazel A.
Abstract : A novel polymorph of ( E )‐4‐bromo‐2‐[(phenylimino)methyl]phenol is reported, with a dihedral angle between the planes of the two aromatic rings of 45.6 (1)°, significantly different to that of the previously published polymorph. The structure contains an intramolecular O—H…N hydrogen bond forming an S (6) ring. Abstract : A new polymorph of ( E )‐4‐bromo‐2‐[(phenylimino)methyl]phenol, C13 H10 BrNO, is reported, together with a low‐temperature structure determination of the previously published polymorph. Both polymorphs were found to have an intramolecular O—H…N hydrogen bond between the phenol OH group and the imine N atom, forming an S (6) ring. The crystals were observed to have different colours at room temperature, with the previously published polymorph being more orange and the new polymorph more yellow. The planarity of the molecule in the two polymorphs was found to be significantly different, with dihedral angles (Φ) between the two aromatic rings for the previously published `orange' polymorph of Φ = 1.8 (2)° at 120 K, while the new `yellow' polymorph had Φ = 45.6 (1)° at 150 K. It was also observed that both polymorphs displayed some degree of thermochromism and upon cooling the `orange' polymorph became more yellow, while the `yellow' polymorph became paler upon cooling.